Use, effectiveness and tolerability of budesonide‐MMX in ulcerative colitis: A real‐life experience. Issue 9 (1st November 2019) - Maconi, Giovanni; Mezzina, Nicolò; Landi, Stefano; Grillo, Simone; Bezzio, Cristina; Bosani, Matteo; Pastorelli, Luca; Dell'Era, Alessandra; Chibbar, Richa; Carmagnola, Stefania; Molteni, Paola; Cassinotti, Andrea; et al.
Abstract : Background: Budesonide‐MMX has an established role in the management of relapsing mild‐to‐moderate ulcerative colitis. Data regarding effectiveness and tolerability in real‐life clinical practice are limited. Aim: The aim of this study was to assess the use of budesonide‐MMX in ulcerative colitis, as well as short‐term effectiveness and tolerability in real‐life practice. Methods: We conducted a retrospective study of adult patients with mild‐to‐moderate ulcerative colitis treated with budesonide‐MMX at four tertiary inflammatory bowel disease centres in Italy from June 2016 to February 2018. Demographic and clinical features of patients, the use of budesonide‐MMX, disease course and concomitant therapy were recorded. The primary outcome assessed was clinical remission at 2 months. Results: A total of 82 patients with active mild‐to‐moderate ulcerative colitis were included in the study with a mean age of 45.9 years and a median partial Mayo Score of 4 (interquartile range 3–5). A total of 41 patients were male. Overall, 36 had extensive colitis, 38 left‐sided colitis and eight proctitis. Treatments at the time of inclusion included 10 patients receiving biologic therapy, seven azathioprine and 54 mesalazine or salazopyrin. The main reasons for the addition of budesonide‐MMX were clinical relapse (47.5%) or inadequate response to current therapy (39.0%). In total, 50% of patients achieved clinical remission, whereas 9.8% had clinical improvement. No response was noted in 40.2% of subjects. Using multivariate binary logistic regression, a moderate degree of activity was the main independent predictor of non‐response. Eight significant adverse effects were reported in six patients with three discontinuing treatment. Conclusion: In real‐life clinical practice, budesonide‐MMX is commonly used in combination with other therapies, both for acute disease flares and for partial response to therapy.